Beyond Technology: A Narrative Review of Organizational Dynamics in IT Change Management - Noviany , Henny (Indonesian Scientific Publication, 2024)
This narrative review examines the organizational, technological, and human factors shaping IT-enabled change management (ITCM), with a particular focus on healthcare systems. The objective is to synthesize current evidence and highlight strategies that facilitate successful digital transformation across diverse contexts. A structured search was conducted in Scopus, Web of Science, PubMed, and Google Scholar, covering studies published between 2013 and 2023. Literature was selected based on relevance to ITCM, organizational readiness, stakeholder engagement, and implementation outcomes. A thematic analysis was applied to identify critical success factors and systemic challenges. Key findings indicate that adaptive organizational culture, strong leadership, and early stakeholder involvement are essential enablers of ITCM. Technological factors such as interoperability and system complexity remain major barriers, often compounded by user resistance. Human resource readiness—particularly digital literacy and training—emerges as a cornerstone of successful adoption. Comparative insights reveal that high-income countries benefit from robust infrastructure and governance, while low- and middle-income countries face persistent barriers related to limited resources and uneven capacity. The review concludes that ITCM requires integrated and context-sensitive strategies that combine technological innovation with organizational adaptability and human capital development. Practical implications include leadership training, cross-functional engagement, and targeted capacity building. Future research should employ longitudinal and system-dynamics approaches to assess sustainability and unintended consequences. This review contributes an integrative framework for understanding ITCM across organizational, technological, and socio-economic dimensions, offering insights for both policy and practice.